CCAFS Midline Household Survey Ghana GH01 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
This dataset contains results of the household survey carried out in the CCAFS research site in northern Ghana in 2018. This midline exercise used the same survey instrument as the baseline survey for comparability. Topics covered include demographics, farm characteristics, food security, climate information, group membership and asset ownership.